(Re)-wiring a brain with light: Clinical and visual processing findings after application of specific coloured glasses in patients with symptoms of a visual processing disorder (CVPD): Challenge of a possible new perspective?. (August 2017) - Friederichs, Edgar; Wahl, Siegfried
Abstract: The present investigation examined whether changes of electrophysiological late event related potential pattern could be used to reflect clinical changes from therapeutic intervention with coloured glasses in a group of patients with symptoms of central visual processing disorder. Subjects consisted of 13 patients with average age 16 years (range 6–51 years) with attention problems and learning disability, respectively. These patients were provided with specified coloured glasses which were required to be used during day time. Results indicated that specified coloured glasses significantly improved attention performance. Furthermore electrophysiological parameters revealed a significant change in the late event related potential distribution pattern (latency, amplitudes). This reflects a synchronization of together firing wired neural assemblies responsible for visual processing, suggesting an accelerated neuromaturation process when using coloured glasses. Our results suggest that the visual event related potentials measures are sensitive to changes in clinical development of patients with deficits of visual processing wearing appropriate coloured glasses. It will be discussed whether such a device might be useful for a clinical improvement of distraction symptoms caused by visual processing deficits. A model is presented explaining these effects by inducing the respiratory chain of the mitochondria such increasing the low energy levels of ATP of our patients.